Actions to Control Hypertension Among Adults in Oklahoma - Jennifer L. Han, PhD (Centers for Disease Control and Prevention, 2011)
IntroductionHypertension is a chronic condition that can be managed with self-monitoring, lifestyle changes, and medication. The purpose of this study was to describe receipt of physician's treatment advice and use of treatments to manage hypertension among Oklahoma's adult population.MethodsA random-digit-dialed telephone survey was administered to noninstitutionalized adult residents of Oklahoma (n = 7,463) in 2007. Respondents who indicated that they had ever had hypertension (n = 2,937) were asked whether a doctor had advised them on each of 5 general management techniques and whether they used these techniques to manage their condition. Data were weighted and a descriptive analysis of the age-adjusted rates was performed.ResultsOf all hypertensive adults, 91% had received advice from a physician regarding treatment options, and medication was the most commonly recommended therapy (80%). Almost all hypertensive adults were managing their hypertension through use of medication or lifestyle modification, and reducing salt intake was the most common treatment used (74%). Physician advice and individual treatment choices varied by demographic characteristics, although respondents more commonly used a treatment method that was advised by a physician.ConclusionDoctors should advise hypertensive patients of treatment options because patients may be more likely to use 1 or more physician-advised options to manage their condition. Efforts should be made to enhance physicians' ability to educate patients about the effects of hypertension and ways in which hypertension can be treated, in addition to enhancing the patients' knowledge of prevention and treatment strategies.